A multimodel assessment of the influence of regional anthropogenic emission reductions on aerosol direct radiative forcing and the role of intercontinental transport. Issue 2 (25th January 2013) - Yu, Hongbin; Chin, Mian; West, J. Jason; Atherton, Cynthia S.; Bellouin, Nicolas; Bergmann, Dan; Bey, Isabelle; Bian, Huisheng; Diehl, Thomas; Forberth, Gerd; Hess, Peter; Schulz, Michael; et al.
Abstract : [1] In this study, we assess changes of aerosol optical depth (AOD) and direct radiative forcing (DRF) in response to the reduction of anthropogenic emissions in four major pollution regions in the Northern Hemisphere by using results from nine global models in the framework of the Hemispheric Transport of Air Pollution (HTAP). DRF at top of atmosphere (TOA) and surface is estimated based on AOD results from the HTAP models and AOD‐normalized DRF (NDRF) from a chemical transport model. The multimodel results show that, on average, a 20% reduction of anthropogenic emissions in North America, Europe, East Asia, and South Asia lowers the global mean AOD (all‐sky TOA DRF) by 9.2% (9.0%), 3.5% (3.0%), and 9.4% (10.0%) for sulfate, particulate organic matter (POM), and black carbon (BC), respectively. Global annual average TOA all‐sky forcing efficiency relative to particle or gaseous precursor emissions from the four regions (expressed as multimodel mean ± one standard deviation) is −3.5 ± 0.8, −4.0 ± 1.7, and 29.5 ± 18.1 mW m −2 per Tg for sulfate (relative to SO2 ), POM, and BC, respectively. The impacts of the regional emission reductions on AOD and DRF extend well beyond the source regions because of intercontinental transport (ICT). On an annual basis, ICT accounts for 11 ± 5% to 31 ± 9% of AOD and DRF in a receptor region at continental or subcontinental scale, with domestic emissions accounting for the remainder, depending on regions and species. For sulfate AOD, the largest ICT contribution of 31 ± 9% occurs in South Asia, which is dominated by the emissions from Europe. For BC AOD, the largest ICT contribution of 28 ± 18% occurs in North America, which is dominated by the emissions from East Asia. The large spreads among models highlight the need to improve aerosol processes in models, and evaluate and constrain models with observations. Key Points: Multi‐model assessment of AOD change due to man‐made emission reductions Intercontinental transport contribution ranges from 11 to 31% 36% of BC AOD in NA and 30% of sulfate AOD in SA come from outside